Introduction to Bachelor of Science in Nursing (Supplementary Programme) in Macau. - Zeng W (Macau Journal of Nursing, 2008)
To introduce the curriculum design, quality control, and teaching activities of the Bachelor of Science in Nursing (Supplementary Programme) in Macau. The findings will help to inform future improvement of the BSNS programme and development of advanced programme.